Industrial Training Report: Perbadanan Perpustakaan Awam Selangor (PPAS) / Noraina Mohd Arifin - Mohd Arifin, Noraina (Faculty of Information Management, 2015)
Public library is a library are located at every stated. Public library maintained and support for public use. It was non-profit library that are give service and facilities to the users. It also gives a service and facilities to all range of ages. People always thinking library is a boring and dull place. With technology and world without boundaries, most of the public library especially at the oversea they having a variety of the service and facilities to make user are like to go the library. At Malaysia, there is less awareness about the advantages of the library. Perbadanan Perpustakaan Awam Selangor (PPAS) take an action with create a zone for the children which is "Zon Kreatif' to make user especially children like to go to the library.